Los nombramientos de cargos para los oficios de plateros y batihojas por el cabildo de Quito (1650-1700) - Paniagua Pérez, Jesús (Estudios humanísticos. Geografía, historia y arte, 1995)
In our work an attempt is made to describe the nominations traditionally performed by the Council of the City of Quito during the first days of each year. Through this we are able to gain a better grasp of the guild organisation in that city during a period not hitherto the subjet of much research, the second half of the seventeenth century.